2021
DOI: 10.1038/s41586-021-03825-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for DarT ADP-ribosylation of a DNA base

Abstract: ADP-ribosyltransferases (ARTs) utilise NAD + to catalyse substrate ADP-ribosylation 1 , thereby regulating cellular pathways or contributing to toxin-mediated pathogenicity of bacteria [2][3][4] . Reversible ADP-ribosylation has traditionally been considered a protein-specific modification 5 , but recent in vitro studies have suggested nucleic acids as targets [6][7][8][9] . Here, we present evidence that specific reversible DNA ADP-ribosylation on thymidine bases occurs in cellulo through the DarT/DarG toxin/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 45 publications
1
68
0
1
Order By: Relevance
“…The heavy focus on ADP-ribosylation as protein modification may have just overshadowed the richness of ADP-ribosylation as general ( protein-unrelated) signalling event. Its study will not only uncover exciting facets of life and evolution but also comes with great potential for the development of new antimicrobials and anticancer agents as well as biotechnological tools [73][74][75]77,78]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heavy focus on ADP-ribosylation as protein modification may have just overshadowed the richness of ADP-ribosylation as general ( protein-unrelated) signalling event. Its study will not only uncover exciting facets of life and evolution but also comes with great potential for the development of new antimicrobials and anticancer agents as well as biotechnological tools [73][74][75]77,78]…”
Section: Discussionmentioning
confidence: 99%
“…2.9 revealed that DarT links ADP-ribose with the anomeric carbon of the adenine-distal ribose to the in-ring nitrogen of the thymidine base. The reaction requires an additional catalytic arginine residue in the active site that is assumed to be particularly essential for proton abstraction from the thymine nitrogen and that extends the canonical set of so far known ART catalytic residues [ 77 ]. It is indicative for the evolving diversity of ARTs with their ability to adapt to versatile specialised functions unrelated to the classical protein-targeting activity.…”
Section: Adp-ribosylation Of Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Initially, PARP activity was measured through incorporation of a radioactive ATP into an acid-insoluble material, although the nature of this product of the DNA-dependent enzyme PARP1 was not known at this stage. [3] Later, an assay method to detect PARP protein and PARP activity directly from nitrocellulose blots using radiolabeled substrate [ 32 P]NAD + was developed by Simonin et al [15] The low-throughput Western blot or dot blot methods have been used with other detection methods including biotinylated NAD + analogs [16] and streptavidin coupled HRP, PAR H10, or MAR/PAR antibodies [17][18][19] and various ADP-ribosylation affinity reagents developed recently. [20][21][22][23] It is noteworthy that when using purified proteins, it is possible to see the disappearance of a protein band upon addition of NAD + with a simultaneous appearance of a high molecular weight smear on a coomassie stained SDS-PAGE.…”
Section: Introductionmentioning
confidence: 99%
“…This modification is readily detectable on a gel when small oligonucleotides are used as targets. [18,19,25,26] Interpretation of the modification by mass spectrometry (MS) proves difficult due to the lack of sequence specificity and presence of multiple modification sites per target protein. Toxins however are sequence specific and modify typically only certain residues in the target proteins and therefore MS spectra is easy to interpret.…”
Section: Introductionmentioning
confidence: 99%